The Relationship of The Nurse's Handover Process With Implementation of Patient Safety Targets in The Surgery Room and Icu - Nathania Pamphila; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Every year, millions of patients suffer injuries or die because of unsafe and Not Good-quality health care. Many medical practices and healthcare-related risks have emerged as major challenges to patient safety and contribute significantly to the burden of harm from unsafe care. The aim of this research is to determine the relationship between the nurse handover process and the implementation of patient safety targets in the surgical ward and ICU of the Royal Prime Hospital Medan 2022. This research is a type of quantitative research with a pre-experimental design method type one group pretest-posttest (single group initial test-final test), with a population of all nurses working in the surgical ward (26 nurses) and ICU (26 nurses). 25 nurses) Royal Prime Hospital Medan, totaling 51 people. Research sample collection techniques are primary data, secondary data and tertiary data. The instrument used is a questionnaire. Research data analysis is univariate analysis and bivariate analysis. The results of the research showed that there was a significant increase in the implementation of the nurse handover process before the treatment was 24.75 and it increased after the treatment to 39.22. Shows that there was a significant increase in the implementation of patient safety targets before treatment, amounting to 27.65 and an increase after treatment to 43.39. And showing a p value (0.005) < 0.05, it shows that there is a significant relationship between the handover process and the implementation of patient safety targets at the RSU. Royal Prima Medan in 2022.Keyword : Handover, Hospital, Patient Safety